Between the lines literary transnationalism and African American poetics - Callahan, Monique-Adelle. (New York ; Oxford : Oxford University Press, 2011)
This work examines the role of women poets of African descent in shaping the history of the Americas. Focusing on three women whose poetry wrestled with the sociopolitical predicaments of the late 19th century, the book ventures a broader definition of African American literature by placing it in a hemispheric context.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Poetry -- Black authors; America -- Literatures -- History and criticism; Transnationalism in literature; Poetics -- History; Slavery in literature; Postcolonialism in literature; Harper, Frances Ellen Watkins, -- 1825-1911 -- Criticism and interpretation; Ayala, Cristina, -- b. 1856 -- Criticism and interpretation; Souza, Auta de, -- 1876-1901 -- Criticism and interpretation